2020
DOI: 10.1002/micr.30574
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve repair throughout the body with processed nerve allografts: Results from a large multicenter study

Abstract: Background Peripheral nerve damage resulting in pain, loss of sensation, or motor function may necessitate a reconstruction with a bridging material. The RANGER® Registry was designed to evaluate outcomes following nerve repair with processed nerve allograft (Avance® Nerve Graft; Axogen; Alachua, FL). Here we report on the results from the largest peripheral nerve registry to‐date. Methods This multicenter IRB‐approved registry study collected data from patients repaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…In 2020 Safa et al [ 64 ], and Leckenby et al [ 65 ] released the latest data from the RANGER study. Safa et al, 2020 [ 64 ] analyzed 624 nerve repairs in 385 subjects. Nerve gap length variated by 1.5–7.0 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020 Safa et al [ 64 ], and Leckenby et al [ 65 ] released the latest data from the RANGER study. Safa et al, 2020 [ 64 ] analyzed 624 nerve repairs in 385 subjects. Nerve gap length variated by 1.5–7.0 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical results following Axogen Avance ® engraftment are encouraging. Most reviewed studies were able to achieve a meaningful recovery in upper 8th percentile of all cases [ 55 , 57 , 58 , 60 , 62 , 63 , 64 ]. Satisfactory motor recovery was reported in 40.1% to 74%.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two decellularised human nerve grafts have undergone multicentre clinical evaluations; a non-commercial nerve graft for sensory nerve defects in China ( He et al, 2015 ) and the commercial Avance ® nerve graft from Axogen in the United States ( Kasper et al, 2020 ; Safa et al, 2020 ). Both are sterilised with 25 kGy gamma radiation; however, it is unclear why this method was selected, and limited data are available regarding the effects of the sterilisation process in isolation on the properties of the decellularised nerve tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several large multicenter studies have demonstrated the efficacy of PNA in peripheral nerve repair throughout the body. 1,18 Most recently, Safa et al reported 624 repairs of peripheral nerve injuries, with an overall meaningful recovery of 82% of patients across sensory, mixed, and motor nerves with gaps up to 70 mm. 18 The vast majority of these repairs were upper and lower extremity, with relatively few head and neck repairs included; however, within the head and neck data, all sensory and motor repairs reported meaningful recovery.…”
Section: Current Literaturementioning
confidence: 99%